Pemberdayaan Masyarakat Kelurahan Sungai Pagar Melalui Pelatihan Pembuatan Briket dari Biomassa Pelepah Kelapa Sawit dalam Kegiatan PPK Ormawa Himagrotek - Naim, Candra Abshar; Sinaga, Gloria Filya; Limbong, Meilisa Sola Gratia; Aisyah, Rahma; Pohan, Dyo Fatarullah; Saputra, M Oji; Manurung, Kezia Eunike; Sabrina, Sabrina; Safputra, Abidzul; Nababan, Leonardo Stepanus; Damanik, Ade Ayu Miranda; Yunandra, Yunandra; Lubis, Nursiani (Unri Conference Series: Community Engagement, 2024)
Sungai Pagar, Lower Kampar Kiri District, Kampar Regency has high potential for oil palm production. One of the challenges is the abundance of palm frond waste in the plantation environment which has a negative impact, especially on the environment. PPK Ormawa Himagrotek Unri conducts training in making briquettes from palm frond waste as a form of community empowerment which aims to increase community knowledge about making briquettes from palm fronds, increase public awareness about the importance of environmental conservation, and improve the economy of the Sungai Pagar Village community. The method used in this activity is Participatory Rural Appraisal (PRA) in increasing awareness and actualization of environmentally friendly behavior of the community through developed institutions. Before the training, the community's knowledge about making briquettes from palm fronds was only 17.3 %. After the training, community knowledge about briquette making increased to 100%. Based on the PPK Ormawa briquetting training program, it is hoped that the Sungai Pagar Village community can utilize the potential of oil palm frond waste to improve the economy and also preserve the environment.